Application of Spiritual Intelligence-Based Curriculum: A Case Study of Boarding School MAN 2 Kudus - Saliyo Saliyo; Adri Efferi; Saefudin Saefudin (Ta'dib, 2024)
This study aims to describe the impact of implementing a spiritual intelligence-based curriculum at the Boarding School "Daarul Adzkiya," MAN 2 Kudus. This type of research is a qualitative research in the category of case studies. Data collected in this study were interviews, observations, documentation, and triangulation. The sampling informants used nonprobability sampling and determination used purposive sampling. The steps of analysis in this study are to describe experience and meaning informant. The results of the analysis show that: (1) the spiritual intelligence-based curriculum at the Boarding School is carried out through scheduled learning and habituation and is fully monitored for 24 hours. The activity begins with the habit of tahajjud prayers to recite the Quran. The meaning gained from self-habituation and learning is independence and self-confidence. (2) The implementation of a spiritual intelligence-based curriculum is supported by: a) teachers who are engaged in linear learning with the disciplines they have and are responsible for their duties; b) input students are selected using the Academic Potential Test; and c) boarding is equipped with hardware and software to support the implementation of the curriculum. Among the impediments are: a) the slow adjustment process of new learners who have never experienced boarding; and b) the insufficient number of caregivers: one versus 40. (3) The curriculum, based on spiritual intelligence, has helped students reach many national and even international goals. Many boarding school graduates have also been accepted into top public universities like UGM, UNDIP, ITS, and ITB.